How healthcare professionals respond to parents with religious objections to vaccination: a qualitative study - Ruijs Wilhelmina LM; LA Hautvast Jeannine; van IJzendoorn Giovanna; van Ansem Wilke JC; Elwyn Glyn; van der Velden Koos; Hulscher Marlies EJL (BMC, 2012)
Abstract Background In recent years healthcare professionals have faced increasing concerns about the value of childhood vaccination and many find it difficult to deal with parents who object to vaccination. In general, healthcare professionals are advised to listen respectfully to the objections of parents, provide honest information, and attempt to correct any misperceptions regarding vaccination. Religious objections are one of the possible reasons for refusing vaccination. Although religious objections have a long history, little is known about the way healthcare professionals deal with these specific objections. The aim of this study is to gain insight into the responding of healthcare professionals to parents with religious objections to the vaccination of their children. Methods A qualitative interview study was conducted with health care professionals (HCPs) in the Netherlands who had ample experience with religious objections to vaccination. Purposeful sampling was applied in order to include HCPs with different professional and religious backgrounds. Data saturation was reached after 22 interviews, with 7 child health clinic doctors, 5 child health clinic nurses and 10 general practitioners. The interviews were thematically analyzed. Two analysts coded, reviewed, discussed, and refined the coding of the transcripts until consensus was reached. Emerging concepts were assessed using the constant comparative method from grounded theory. Results Three manners of responding to religious objections to vaccination were identified: providing medical information, discussion of the decision-making process, and adoption of an authoritarian stance. All of the HCPs provided the parents with medical information. In addition, some HCPs discussed the decision-making process. They verified how the decision was made and if possible consequences were realized. Sometimes they also discussed religious considerations. Whether the decision-making process was discussed depended on the willingness of the parents to engage in such a discussion and on the religious background, attitudes, and communication skills of the HCPs. Only in cases of tetanus post-exposure-prophylaxis, general practitioners reported adoption of an authoritarian stance. Conclusion Given that the provision of medical information is generally not decisive for parents with religious objections to vaccination, we recommend HCPs to discuss the vaccination decision-making process, rather than to provide them with extra medical information.